Wide-range CRP versus high-sensitivity CRP on Roche analyzers: focus on low-grade inflammation ranges and high-sensitivity cardiac troponin T levels. (4th July 2018) - Monneret, Denis; Mestari, Fouzi; Djiavoudine, Shaedah; Bachelot, Guillaume; Cloison, Maxime; Imbert-Bismut, Françoise; Bernard, Maguy; Hausfater, Pierre; Lacorte, Jean-Marc; Bonnefont-Rousselot, Dominique
Abstract: Wide-range C-reactive protein (wr-CRP) has been proposed as an economical alternative to high-sensitivity C-reactive protein (hs-CRP) for the evaluation of low-grade inflammation-associated cardiovascular risk (LGI-CVR). Concomitant values of serum hs-CRP and plasma wr-CRP ≤5 mg/L, and high-sensitivity cardiac troponin T (hs-cTnT), all assayed on Roche Diagnostics analyzers over a 1.8-year period, were extracted from a hospital laboratory database. Hs-CRP and wr-CRP values were compared (Bland–Altman method; Deming's correlation), then separately classified into low (<1 mg/L), moderate (1–3 mg/L) and high (>3 mg/L) LGI-CVR ranges for agreement test (κ), assessed before and after Deming's regression-based adjustment of wr-CRP (Adj-wr-CRP). Wr-CRP and hs-CRP values were strongly correlated, with linearity, whether below 5 mg/L ( n  = 744; τ = 0.933; p  < .001) or below 1 mg/L ( n  = 283; τ = 0.823; p  < .001). Overall, wr-CRP values were lower than hs-CRP (mean bias: –0.11 ± 0.17 mg/L). Agreement was good, with 8.1% of wr-CRP values misclassified compared to hs-CRP (κ: 0.874), and weakly improved after regression-based adjustment (7.7% reclassified values; κ: 0.881). Lowering the Adj-wr-CRP cutoff of the moderate LGI-CVR subrange from 1.0 to 0.9 mg/L resulted in an almost perfect agreement (3.2% reclassified data; κ: 0.950). Hs-cTnT concentration was positively associated with hs-CRP, wr-CRP, and Adj-wr-CRP ( p  < .001). Within each LGI-CVR subrange, hs-cTnT medians were similar regardless of the hs-CRP, wr-CRP or Adj-wr-CRP used for risk classification. Based on hs-cTnT, this study supports the use of wr-CRP as a low-cost alternative to hs-CRP for cardiovascular risk evaluation.